2020
DOI: 10.1021/acsinfecdis.0c00368
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutically Acceptable Carboxylic Acid-Terminated Polymers Show Activity and Selectivity against HSV-1 and HSV-2 and Synergy with Antiviral Drugs

Abstract: Polyanionic macromolecules including carboxylate-terminated polymers (polycarboxylates) are capable of inhibiting sexually transmitted viruses such as human immunodeficiency virus (HIV) and herpes simplex virus (HSV). Cellulose acetate phthalate (CAP), a pharmaceutically acceptable pH-sensitive polycarboxylate polymer, showed promising prophylactic activity against HIV and HSV, but the instability of CAP in an aqueous environment prevented its clinical development. Interestingly, several pharmaceutically accep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 44 publications
1
9
0
1
Order By: Relevance
“…Decoying polymeric scaffolds with carboxylate and carboxylic acid moieties have been shown to introduce antiviral activity by inhibiting the viral entry to the host cells. , It has been shown that the FDA-approved cellulose acetate phthalate in the regular and nanoparticle (NP) form has selectivity and antiviral activity against HSV types 1 and 2, although their exact mechanism of action is under further investigation …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Decoying polymeric scaffolds with carboxylate and carboxylic acid moieties have been shown to introduce antiviral activity by inhibiting the viral entry to the host cells. , It has been shown that the FDA-approved cellulose acetate phthalate in the regular and nanoparticle (NP) form has selectivity and antiviral activity against HSV types 1 and 2, although their exact mechanism of action is under further investigation …”
Section: Introductionmentioning
confidence: 99%
“…19,20 It has been shown that the FDA-approved cellulose acetate phthalate in the regular and nanoparticle (NP) form has selectivity and antiviral activity against HSV types 1 and 2, although their exact mechanism of action is under further investigation. 21 Negatively charged polysaccharides, with similar structures to HS like heparin, have been used as binding decoys to prevent HSV-1 infection. 22,23 However, clinical application of heparin as an antiherpetic drug is limited because of its heterogeneity and possible impurities.…”
Section: ■ Introductionmentioning
confidence: 99%
“… 218 Whereas HPMCP-55S was active against both HSV-1 and HSV-2, PVAP only showed neutralizing activity against HSV-1 infections, while Eudragit S100 only showed significant antiviral efficacy against HSV-2, indicating a potential selectivity of the different polyanions against different viruses. 218 …”
Section: Hs Mimetics As Viral Inhibitorsmentioning
confidence: 98%
“…Shortly after this study, Yadavalli and co-workers demonstrated that three previously FDA-approved polycarboxylates used for coating drugs in oral formulations,PVAP (poly­(vinyl acetate phthalate)), HPMCP-55S (hydroxypropyl­methylcellulose phthalate), and Eudragit S100 (methacrylic acid methyl methacrylate copolymer, ratio 1:2)exhibited antiviral activity against HSV infections . Whereas HPMCP-55S was active against both HSV-1 and HSV-2, PVAP only showed neutralizing activity against HSV-1 infections, while Eudragit S100 only showed significant antiviral efficacy against HSV-2, indicating a potential selectivity of the different polyanions against different viruses …”
Section: Hs Mimetics As Viral Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation